Relationship between demographic variables and collegiate athletes` perceptions of social support from head coaches - Newman, N. D.; Weiss, W. M. (International Journal of Sports Science & Coaching, 2018)
Previous research has demonstrated the importance of social support during the rehabilitation of an injury. In particular, athletes view coaches as a primary source of social support. However, coaches have been an inconsistent or insufficient source of social support. Certain demographic variables may be related to differences in perceived social support from coaches. The purpose of this study was to describe injured collegiate athletes` perceptions of social support and explore whether differences in perceived social support from coaches existed due to contextual or situational factors. A survey on perceived social support from coaches was completed by athletes (n?=?246) at five NCAA institutions. Results support previous findings that injured athletes perceive coaches as sources of moderate to high amounts of social support. Additionally, significant differences emerged in perceived social support based on the level of competition and type of sport. These results reaffirm the role head coaches play in the rehabilitation of injured athletes. Understanding variables that influence how an athlete perceives social support from a coach could improve rehabilitation outcomes.